'It's like half-sport, maybe even a bit more than half-sport': children's experience of a sport for all programme in school. Issue 2 (2nd April 2016) - Carlman, Peter; Augustsson, Christian
Abstract: In this article we explore children's experiences of a Sport for All Programme (SAP) in school. The purpose of the 'Sport for All' policy is to give children an opportunity to try different sports, with a focus on play and motor learning rather than organized competition. In this study, we approach children as active agents in constructing the SAP practice in line with the theoretical standpoint that children are competent social actors with agency. The study is based on repeated focus group interviews with 15 ten-year-old children (9 girls, 6 boys) participating in a SAP in the western part of Sweden. The children perceived the SAP as sessions with less emphasis on performance and without organized competitions; it was described as a 'low threshold' activity. However, the result showed that the SAP activity was not free from performance-oriented principles. The Sport for All pedagogy needs to consider and handle the consequences of competition principles, especially if the participating children and leaders have a performance ethos.